2023
DOI: 10.1302/0301-620x.105b1.bjj-2022-0812.r1
|View full text |Cite
|
Sign up to set email alerts
|

Thin highly cross-linked polyethylene liners combined with large femoral heads in primary total hip arthroplasty show excellent survival and low wear rates at a mean follow-up of 12.8 years

Abstract: Aims Several short- and mid-term studies have shown minimal liner wear of highly cross-linked polyethylene (HXLPE) in total hip arthroplasty (THA), but the safety of using thinner HXLPE liners to maximize femoral head size remains uncertain. The objective of this study was to analyze clinical survival and radiological wear rates of patients with HXLPE liners, a 36 mm femoral head, and a small acetabular component with a minimum of ten years’ follow-up. Methods We retrospectively identified 55 patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In THA using sequentially irradiated and annealed HXLPE (X3; Stryker), the mean linear wear rate was 0.02 ± 0.03 mm/y with a mean follow-up of 10 years, and the all-cause survival rate was 92% [ 79 ]. Another study demonstrated that the mean linear wear rate was 0.085 mm, and the overall survival rate for all-cause revision was 95% at a mean follow-up of 13 years [ 80 ]. The long-term results were excellent, although in vivo oxidation has been reported [ 81 , 82 ].…”
Section: Clinical Results With Second-generation Hxlpementioning
confidence: 99%
“…In THA using sequentially irradiated and annealed HXLPE (X3; Stryker), the mean linear wear rate was 0.02 ± 0.03 mm/y with a mean follow-up of 10 years, and the all-cause survival rate was 92% [ 79 ]. Another study demonstrated that the mean linear wear rate was 0.085 mm, and the overall survival rate for all-cause revision was 95% at a mean follow-up of 13 years [ 80 ]. The long-term results were excellent, although in vivo oxidation has been reported [ 81 , 82 ].…”
Section: Clinical Results With Second-generation Hxlpementioning
confidence: 99%
“…This finding aligns with previous studies that demonstrated that total head penetration and wear rates are independent from femoral head size. [27][28][29] No patients experienced aseptic loosening, and only one underwent revision due to dislocation two days after surgery. Given that the THA lifespan is usually 20 years, 2,14 the sample size was small, and the wear rate was low, other revisions would have been unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…This interesting single-centre study from a team in Vancouver (Canada) included only a few patients, but with radiological measures of linear and volumetric wear. 4 The authors identified 55 patients, all receiving a total hip arthroplasty using HXLPE liners combined with 36 mm cobalt-chrome heads in acetabular components with an outer diameter of 52 mm or smaller. Of the original 55 patients, 22 had a minimum radiological follow-up of seven years and were assessed radiologically for linear and volumetric wear.…”
Section: Can You Maximize Femoral Head Size At the Expense Of Liner T...mentioning
confidence: 99%